IMPLEMENTASI RFID PADA SISTEM INFORMASI PRESENSI SISWA DI MAS AL-HUDA KANGAYAN DENGAN NOTIFIKASI WHATSAPP GATEWAY - Moh. Baha'Uddin Hidayat; Adi Susanto; A. Hamdani (LPPM Universitas Abdurrab, 2025)
Student attendance is a crucial component of academic administration, serving to monitor student discipline and as the basis for attendance reporting to parents. At MAS Al-Huda Kangayan, the attendance recording process is still conducted manually using physical documents and Excel files, making it prone to errors, delays in recapitulation, and limited real-time access to information. This study aims to implement an RFID-based student attendance information system integrated with a WhatsApp Gateway, as an effort to improve efficiency, accuracy, and transparency in attendance recording. The system was developed using the Waterfall method, which includes the stages of requirement analysis, system design, implementation, and testing. The implementation results show that the system is capable of automatically recording attendance in real time and sending notifications directly to parents via the WhatsApp platform. Based on the test results, the system successfully reduced the average attendance recording time from 3.5 minutes to approximately ±35 seconds for a class of 10 students, equivalent to an efficiency improvement of around ±83%. Thus, the system has proven to be effective in accelerating the attendance process, minimizing recording errors, and enhancing parental involvement in monitoring student attendance.